Hakikat Pendidikan Kristen Dalam Gereja - Delpi Novianti (Pusat Riset dan Inovasi Nasional, 2024)
The church is a community of people who believe in Christ. Christ's atonement for every believer should be a means of self-actualization that is superior in terms of character, nature, and critical thinking towards everything, so that he can live his life wisely in the midst of this world. Therefore, every believer needs to be equipped with planned, directed and continuous guidance in order to give birth to every member of the congregation who is spiritually and physically established. To achieve this noble hope, Christian education in the church is the right space to develop and guide every believer to become a people who can respond to God's call on their lives according to their talents and abilities. Therefore, the church is expected to be able to actualize its role in developing the people through Christian education. Christian education is expected to be able to provide understanding to church members so that they can use Christian education as a basis and means for forming people into members of God's kingdom, who are able to be salt and light in today's world. Christian education is a form of fertilizing the minds of believers with the Word of God under the guidance of the Holy Spirit through a number of learning experiences carried out by the church, for all believers who are discipled to know Jesus Christ. In the study of this topic, it will be discussed as follows: a). The Nature of Christian Education in the Church; b). The Goals of Christian Education in the Church and c). Forms of Christian Education in the Church.